The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.14814/phy2.13545
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C-C Motif) Receptor-Like 2 is not essential for lung injury, lung inflammation, or airway hyperresponsiveness induced by acute exposure to ozone

Abstract: Inhalation of ozone (O3), a gaseous air pollutant, causes lung injury, lung inflammation, and airway hyperresponsiveness. Macrophages, mast cells, and neutrophils contribute to one or more of these sequelae induced by O3. Furthermore, each of these aforementioned cells express chemokine (C‐C motif) receptor‐like 2 (Ccrl2), an atypical chemokine receptor that facilitates leukocyte chemotaxis. Given that Ccrl2 is expressed by cells essential to the development of O3‐induced lung pathology and that chemerin, a Cc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…Regardless of genotype, chemerin, one of two endogenous ligands for CMKLR1, was significantly greater in BAL fluid obtained from O 3 ‐ as compared to air‐exposed mice (Figure 1b ), which is consistent with our previous data (Malik et al., 2017 ; Razvi et al., 2015 ). However, independent of exposure, BAL chemerin was at least three‐fold greater in CMKLR1‐deficient as compared to wild‐type mice, and this observation is not without precedent.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regardless of genotype, chemerin, one of two endogenous ligands for CMKLR1, was significantly greater in BAL fluid obtained from O 3 ‐ as compared to air‐exposed mice (Figure 1b ), which is consistent with our previous data (Malik et al., 2017 ; Razvi et al., 2015 ). However, independent of exposure, BAL chemerin was at least three‐fold greater in CMKLR1‐deficient as compared to wild‐type mice, and this observation is not without precedent.…”
Section: Discussionsupporting
confidence: 92%
“…Differences exist between 7-and 39-week-old mice with regard to O 3 -lung inflammation and antioxidant gene expression (Shore et al, 2011), and thus, age is another plausible explanation as to the reason differences in lung Cmklr1 mRNA expression exist between our study and that of Kilburg-Basnyat et al (2018). Regardless of genotype, chemerin, one of two endogenous ligands for was significantly greater in BAL fluid obtained from O 3 -as compared to airexposed mice (Figure 1b), which is consistent with our previous data (Malik et al, 2017;Razvi et al, 2015). However, independent of exposure, BAL chemerin was at least three-fold greater in CMKLR1-deficient as compared to wild-type mice, and this observation is not without precedent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On days 7, 14, 21, 28 and 33 of the bleomycin treatment regimen, respiratory system mechanics and P–V relationships were measured using the flexiVent (SCIREQ Inc., Montreal, QC, Canada) as previously described (Dahm et al., ; Karmouty‐Quintana et al., , ; Malik et al., ). In brief, the mice were anaesthetized with pentobarbital sodium (50 mg kg −1 , i.p ., Oak Pharmaceuticals, Inc.; Lake Forest, IL, USA) and xylazine hydrochloride (7 mg kg −1 , i.p ., Vedco Inc.; Saint Joseph, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…CCRL2 genetically deficient mouse models have facilitated research on the function of CCRL2 in homeostasis and disease [16,17,[47][48][49], however, studies demonstrating the functional translation to humans are still lacking. While little is known about the function of CCRL2 in monocytes, previous work showed that human CD14 + monocytes express CCRL2 [35,50].…”
Section: Plos Onementioning
confidence: 99%